Automatic segmentation of the lungs in chest computed tomography - Bez, Mag, Marta Rosecler; Ferreira de Oliveira, Ricardo; Freiberger Rönnau, Rodrigo; Flores, Jéferson Cristiano (I+ T+ C- Research, Technology and Science, 2015)
Among the tests that help health professionals and allow the application of computer systems is the Computed Tomography (CT). This article presents the development of a software prototype that can automatically segment the lungs in computed tomography images of the chest. The validation process applied the method on 569 images and showed a success rate of 94,38%. For the cases of error in the process, their causes are shown and enhancements to the prototype are discussed.